2018
DOI: 10.1177/1535370218813909
|View full text |Cite
|
Sign up to set email alerts
|

Leptin induces the expression of tumorigenic genes in the gastric mucosa of male Sprague-Dawley rats

Abstract: Leptin promotes the growth of gastric cancer cells in vitro. It is, however, unknown if leptin induces gastric cancer in vivo. This study therefore investigated the effect of leptin on the histology and expression of tumorigenic genes in the stomach of rats following 40 weeks of leptin treatment. Male Sprague-Dawley rats, aged 6 weeks, were randomized into control and experimental groups ( n = 8 per group). The experimental group was given intraperitoneal injections of leptin (60 µg/kg/day) once daily for 40 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
(43 reference statements)
4
7
0
Order By: Relevance
“…The prevalence of cancer is high in obese individuals where serum leptin levels are also high. Recent reports have also shown that leptin may have both tumorigenic and carcinogen enhancing properties [40,41]. From these recent studies it clearly appears that although leptin is necessary for normal physiological functions, but when present at high levels, it might also contribute to some of the obesity related diseases.…”
Section: Introduction To Leptinmentioning
confidence: 99%
“…The prevalence of cancer is high in obese individuals where serum leptin levels are also high. Recent reports have also shown that leptin may have both tumorigenic and carcinogen enhancing properties [40,41]. From these recent studies it clearly appears that although leptin is necessary for normal physiological functions, but when present at high levels, it might also contribute to some of the obesity related diseases.…”
Section: Introduction To Leptinmentioning
confidence: 99%
“…25 LEP could induce the expression of tumorigenic genes in the gastric mucosa of male rats. 26 Dietary fat-accelerating LEP signaling was shown to promote protumorigenic gastric environment in mice. 27 Overexpression of LEP was linked with the development of GC in humans and murine.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that the IL-8/CXCR1/2 signaling pathway can promote the proliferation and metastasis of various tumor cells [25]. [29]. The above studies indicate that REEP5 has the effect of promoting the occurrence and development of various cancer cells.…”
Section: Discussionmentioning
confidence: 92%